2020
DOI: 10.1038/s41598-020-73603-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum ammonia is a strong prognostic factor for patients with acute-on-chronic liver failure

Abstract: Ammonia is thought to be central to the pathogenesis of hepatic encephalopathy (HE), but its prognostic role in acute-on-chronic liver failure (ACLF) is still unknown. We aimed to determine the association between serum ammonia level and short-term prognosis in ACLF. Furthermore, we performed an in-depth evaluation of the independent effect of serum ammonia level on the short-term prognosis of hepatitis B virus (HBV) reactivation-induced ACLF patients. We identified 174 patients as part of prospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The serum ammonia level has widely been used as a biomarker for the diagnosis and treatment of liver failure, and for identi cation of hepatic associated with hyperammonemia. (34) Treating high serum ammonia levels effectively restores consciousness, attenuates the incidence of cerebral edema, and improves overall morbidity and mortality. However, the clinical signi cance of NHH as a prognostic indicator has long been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The serum ammonia level has widely been used as a biomarker for the diagnosis and treatment of liver failure, and for identi cation of hepatic associated with hyperammonemia. (34) Treating high serum ammonia levels effectively restores consciousness, attenuates the incidence of cerebral edema, and improves overall morbidity and mortality. However, the clinical signi cance of NHH as a prognostic indicator has long been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by Hu et al . [ 36 ] from China who measured ammonia levels in patients with acute-on-chronic liver failure and predicted raised ammonia levels to be an important prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al found that hyperammoniemia was significant in 28-day mortality in acute and chronic liver failure (19).…”
Section: Discussionmentioning
confidence: 99%